Cholangiography after orthotopic liver transplantation - Nöldge, Gerd; Otto, Gerd; Theilmann, Lorenz (Springer Berlin Heidelberg, 1996)
Biliary tract complications are still the major cause of morbidity following orthotopic liver transplantation. This book deals systematically with the large variety of possible cholangiographic changes. The figures are the results of a review of cholangiograms from more than 280 patients who underwent orthotopic liver transplantation. The etiology, clinical aspects, and treatment of these complications are reviewed on the basis of the authors' experience in radiology, endoscopy, and transplant surgery
Keywords: Atlas; Cholangiographie; Lebertransplantation